The Intersections Between Sexual Orientation, Latine Ethnicity, Social Determinants of Health, and Lifetime Suicide Attempts in a Sample Being Assessed for Entry to Co-Occurring Mental Health and Substance Use Disorder Treatment - Akeem Modeste-James; Therese Fitzgerald; Emily Stewart; Diliana De Jesus; Melisa Canuto; Micaurys Guzman; Jessica Mateo; Melinda D'lppolito; Lena Lundgren (SAGE Publishing, 2024)
Purpose: Few studies have examined the relationship between the intersections of lesbian, gay, and bisexual (LGB) sexual orientation, Latine ethnicity, and lifetime suicide attempts in Latine individuals with substance use disorder. This study examines this intersection and controls for social determinants of health, mental health disorder symptoms, and substance use disorder symptoms in a sample of Latine adults entering treatment for co-occurring disorders. Method: Bivariate statistics and multivariate logistic regression were used to analyze assessment data (n = 360) from a bilingual/bicultural integrated behavioral health system serving Latine communities in Massachusetts to examine the relationship between sexual orientation, Latine ethnicity, and history of lifetime suicide attempts. We controlled for social determinants of health, mental health disorders, and substance use disorder (SUD) factors significantly associated with lifetime suicide attempts at the bivariate level. Results: Over 27% of the sample and 35% of Puerto Ricans (PR) reported lifetime suicide attempts. The logistic regression identified that PR clients were 78% more likely to have attempted suicide in a lifetime compared to non-PR clients. Clients identifying as LGB were 3.2 times more likely to report having attempted suicide in their lifetime compared to heterosexual clients. Unemployed clients were 2.4 times more likely to report having attempted suicide in their lifetime compared to employed clients. Conclusion: Findings identify high rates of lifetime suicide attempts among LGBs and PRs entering SUD treatment. Targeted outreach and treatment efforts designed to address intersectionality for this underserved population are needed.